Vapor- and aerosol-phase atmospheric organic matter in urban air of the Midwest USA. (1st November 2021) - Flores, Rosa M.; Doskey, Paul V.
Abstract: Vapor- and aerosol-phase atmospheric organic matter were collected in East St. Louis, MO using the high-volume sampling method. Samples were processed by traditional analytical methods and analyzed by multidimensional gas chromatography with time-of-flight mass spectrometric detection. Levels of identified, hydrocarbon-like organic vapor and aerosol species (i.e., HOV and HOA, respectively) were 10–42 ng m −3 and 0.020–3.6 ng m −3, respectively. Concentrations of identified, oxygenated organic vapor and aerosol species (i.e., OOV and OOA, respectively) were 2–66 ng m −3 and 23–310 ng m −3, respectively. The principal feature of the HOV was an unresolved complex mixture that represented 54.5 ± 11.3% of the total HOVs during the field campaign. Levels of n - and branched alkanes, alkyl and cycloalkylbenzenes, polyaromatic hydrocarbons (PAHs), and alkyl-substituted PAHs generally declined from the morning rush hour to the 1000–1400 sampling period, which was similar to the expected trend in reactivity with respect to OH. The OOV included aliphatic mono-carboxylic acids, aliphatic and aromatic alcohols, aldehydes, and ketones, and alicyclic ketones, alcohols, and epoxides (i.e., montoterpenoids). The bulk of the OA species (∼99%) were a complex mixture of OOA, which included multifunctional n -aliphatic, alicyclic, and aromatic hydrocarbons, dicarboxylic and ketocarboxylic aliphatic and dicarboxylic monoaromatic acids, lactones, tetrols, and pentitols. The sampling and analytic techniques provided quantitative molecular information for HOVs in ambient air, which are a missing source of secondary organic aerosol precursors. Molecular characterization and quantitation of HOVs and OOA species will facilitate predictions of SOA formation using molecular-specific models. Highlights: We measured vapor- and aerosol-phase organic matter with fine temporal resolution. GC × GC-ToF-MS was used for comprehensive organic molecular analysis. Hydrocarbons and an unresolved complex mixture were observed in the vapor phase. Diesel-powered vehicles are an important source of vapor-phase hydrocarbons. Molecular markers of SOA were observed in the aerosol phase.